Pengaruh Leverage dan Good Corporate Governance Governance Terhadap Kinerja Keuangan - Rosa Maria Anjelina Dhone; Siti Ruhana Dara (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of leverage and good corporate governance on the financial performance of the banking sub-sector. The independent variables studied were leverage and good corporate governance which were proxy by the independent board of commissioners, a board of directors, and the audit committee. The population is the banking sub-sector companies listed on the Indonesia Stock Exchange for the period 2015-2019. Samples were selected by purposive sampling technique so that 12 companies were obtained that met the criteria as samples. Data analysis was performed using panel data regression analysis methods. The study provides the results that the board of directors influences the financial performance of the company. While leverage, the independent board of commissioners and the audit committee do not affect the financial performance of the company.